Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1002/hep.1840110202
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic liver transplantation for alcoholic liver disease

Abstract: Alcohol abuse is the most common cause of end-stage liver disease in the United States, but many transplant centers are unwilling to accept alcoholic patients because of their supposed potential for recidivism, poor compliance with the required immunosuppression regimen and resulting failure of the allograft. There is also concern that alcohol-induced injury in other organs will preclude a good result. From July 1, 1982, to April 30, 1988, 73 patients received orthotopic liver transplants at the University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
105
0
8

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(122 citation statements)
references
References 9 publications
6
105
0
8
Order By: Relevance
“…Em 1988, STARZL et al (15) , avaliando 41 pacientes com cirrose alcoólica avançada submetidos a TH na Universidade de Pittsburgh, sob esquema de imunossupressão com ciclosporina, relataram sobrevida em 1 ano de 73,2% e em 3 anos de 68%. Índices satisfatórios de sobrevida em 1 ano pós-TH em portadores de DHA, variando de 66% a 100%, também foram documentados em outros centros americanos e europeus (1,2,5,7,8,9,10,13,14,16) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Em 1988, STARZL et al (15) , avaliando 41 pacientes com cirrose alcoólica avançada submetidos a TH na Universidade de Pittsburgh, sob esquema de imunossupressão com ciclosporina, relataram sobrevida em 1 ano de 73,2% e em 3 anos de 68%. Índices satisfatórios de sobrevida em 1 ano pós-TH em portadores de DHA, variando de 66% a 100%, também foram documentados em outros centros americanos e europeus (1,2,5,7,8,9,10,13,14,16) .…”
Section: Introductionunclassified
“…A freqüência com que a recidiva de consumo de bebidas alcoólicas é detectada no acompanhamento pós-transplante é variável, dependendo em parte dos métodos empregados na avaliação e seleção dos candidatos na fase pré-transplante, bem como dos métodos empregados para tal rastreamento dessa complicação no pós-transplante. Publicações relatando a experiência de diferentes centros transplantadores apontam para índices de recidiva em torno de 12% a 50% (2,6,7,8,9,10,11,13) . A necessidade de intervalo de abstinência pré-TH tem sofrido reavaliações, mas a maioria dos centros de transplante adota mínimo de abstinência de pelo menos 6 meses antes do TH.…”
Section: Introductionunclassified
“…3 We find that many times it is not the surgical threat, or the magnitude of the procedure itself, but the whole process of medical support, which includes invasive procedures to investigate comorbid conditions. If the postoperative abstinence may be related to the regimentation that is required after transplantation, 4 we think that all that is done before is really the key life event that is able to change its course.…”
mentioning
confidence: 99%
“…4 However, and this is rarely needed in our experience, it is essential to be absolutely sure of sustained abstinence through personal and familial interviews or with the not so satisfactory biochemical markers of alcohol use.…”
mentioning
confidence: 99%
“…Data from many centers have shown that liver transplantation is a successful treatment for this syndrome. [2][3][4][5][6][7] The main argument regarding the purpose of liver transplantation in ALD turns on a consideration of alcoholism rather than of liver disease itself. The debate is complicated by the fact that the number of potential recipients for liver transplantation greatly exceeds the number of available donor organs.…”
mentioning
confidence: 99%